Integrated management of foliar diseases of sesame (Sesamum indicum L.): Integrated management of foliar diseases of sesame (Sesamum indicum L.) - NAYAN KISHOR ADHIKARY,; TAMINA BEGUM,; RAMBILASH MALLICK, (Journal of Oilseeds Research, 2020)
In sesame, minimum incidence of Alternaria leaf spot with severity of 10.6 and 7.8% with higher seed yield of514 and 612 kg/ha, respectively were recorded in summer, 2018 and 2019 with spray of carbendazim 12% + mancozeb 63% 75WP @ 2 g/l. Low severity of Cercospora leaf spot 5 and 6.7% with higher seed yield of 509 and 565 kg/ha, respectively were recorded in summer 2018 and 2019 with spray of myclobutanil 10% WP @ 1 g/l.